2017
DOI: 10.29356/jmcs.v58i3.135
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Dehalogenation of Organic Pollutants

Abstract: <p>This review summarizes our own research, published since 2004, dealing with electrochemical reduction of halogenated organic compounds that are environmental pollutants. Included are sections surveying the direct and mediated reduction of the following species: (a) chlorofluorocarbons; (b) pesticides, fungicides, and bactericides; (c) flame retardants; and (d) disinfection by-products arising from the chlorination of water. To provide the reader with a perspective of these topics beyond our own work, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 176 publications
(213 reference statements)
0
32
0
Order By: Relevance
“…Therefore, electrodes with catalytic properties allowing the reductive dechlorination at less cathodic potentials are required. The electrocatalytic reduction of the C‐Cl bond can be achieved on electrodes modified with organometallic catalysts or with metals . Among the different metals that have been studied, silver has been the subject of many investigations since it presents high electrocatalytic activity for the reduction of carbon–chlorine bonds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, electrodes with catalytic properties allowing the reductive dechlorination at less cathodic potentials are required. The electrocatalytic reduction of the C‐Cl bond can be achieved on electrodes modified with organometallic catalysts or with metals . Among the different metals that have been studied, silver has been the subject of many investigations since it presents high electrocatalytic activity for the reduction of carbon–chlorine bonds.…”
Section: Introductionmentioning
confidence: 99%
“…The electrocatalytic reduction of the C-Cl bond can be achieved on electrodes modified with organometallic catalysts or with metals. 18,[23][24][25] Among the different metals that have been studied, silver has been the subject of many investigations since it presents high electrocatalytic activity for the reduction of carbon-chlorine bonds. This property has been attributed to its high electrophilicity due to specific interactions of the C-Cl bond with silver that lowers the driving force of the electron transfer.…”
Section: Introductionmentioning
confidence: 99%
“…10 Interest in the use of electrochemical reduction for detection, degradation, and remediation of halogenated pesticides has prompted a number of investigations, some of which are described in a recent review. 11 In early work by Rosenthal and Lacoste, 12 a polarographic study of a number of aromatic chloroethanes, including methoxychlor, established that electrochemical reduction resulted in cleavage of all three carbon-chlorine bonds. Tandon and co-workers extended this research in their own polarographic studies of the reduction of methoxychlor in aqueous media containing dimethylformamide (DMF) and ethanol, 13 as well as in the presence of various surfactants; 14 it was reported that uptake of six electrons is required for cleavage of the three carbon-chlorine bonds.…”
mentioning
confidence: 99%
“…As a result, it tends to bioaccumulate and has been detected in human blood, breast milk, and adipose tissue from samples taken around the world [67]. Its well-established neurotoxicity, carcinogenicity, and consequent health risks led to a worldwide ban of lindane by the Stockholm Convention in 2007 [68,69]. In fact, some countries are still using it for economic reasons [30,64].…”
Section: Electrochemical Detection Of Lindanementioning
confidence: 99%